2008
DOI: 10.1080/10937400801909002
|View full text |Cite
|
Sign up to set email alerts
|

Human Biomonitoring and the Inspire Directive: Spatial Data as Link for Environment and Health Research

Abstract: Recently, there has been a rapid gain of interest in the availability, applicability, and integration of different types of spatial data for environment and health issues. The INSPIRE Directive (Directive 2007/2/EC) aims at providing better and easily accessible spatial information in Europe for the formulation and implementation of community policy on the environment by triggering the creation of a European spatial information infrastructure that delivers integrated spatial information services to potential u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The biomedical and public health literature on geographic information systems (GIS) and spatio-temporal analyses features a large number of research papers mentioning or addressing location privacy, e.g., [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. A must-read paper (not specifically health-related) dating back to 1994 [29] shows how chronic privacy issues are in GIS research.…”
Section: Research Literature: Location Privacy Concerns and Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomedical and public health literature on geographic information systems (GIS) and spatio-temporal analyses features a large number of research papers mentioning or addressing location privacy, e.g., [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. A must-read paper (not specifically health-related) dating back to 1994 [29] shows how chronic privacy issues are in GIS research.…”
Section: Research Literature: Location Privacy Concerns and Solutionsmentioning
confidence: 99%
“…A must-read paper (not specifically health-related) dating back to 1994 [29] shows how chronic privacy issues are in GIS research. Some research papers identified privacy as a potential or actual issue of concern (e.g., in reproductive health research [18]; in birth defects surveillance and research [19]; in research relevant to policy on diet, physical activity, and weight [20]; in environmental health research [21]; and in health and social care planning [22]), while others went one step further by suggesting some comprehensive solutions (e.g., [23][24][25][26]), workarounds, or frameworks and principles of practice (e.g., [29]) to mitigate or resolve these privacy concerns.…”
Section: Research Literature: Location Privacy Concerns and Solutionsmentioning
confidence: 99%
“…Accuracy in location, however, can lead to cases being identifiable, particularly in small spatial units [17]. The identifiability of cases has been noted as a potential or actual issue of concern in reproductive health [18], birth defects [19], diet [20], environmental health [21], social care planning [22], and geo-privacy studies [23]. The U.S. Privacy Rule of the Health Insurance Portability and Accountability Act (HIPAA) [24] requires that disclosed health information be restricted to the minimum necessary to satisfy its intended purpose.…”
Section: Introductionmentioning
confidence: 99%
“…• Multiple systematic tools for linking exposure, dose and health effect data, such as Geographical Information Systems (GIS) [65], Bayesian belief networks (BBN) [66] and multiple lines and levels of evidence (MLLE) tools [67]. GIS links the indicators from environmental monitoring, biomonitoring and health surveillance in a visual way.…”
Section: Introductionmentioning
confidence: 99%
“…Each feature is linked to a position on the graphical image on a map and a record in an attributed table. Besides simply plotting environmental monitoring data and morbidity/mortality information on a map, GIS also offer important opportunities for interpolation or extrapolation of monitoring and modelling data [65]. MLLE is developed for epidemiological studies, human and ecological risk assessments [68,69].…”
Section: Introductionmentioning
confidence: 99%